Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
ASCILITE 2021: Back to the Future – ASCILITE ‘21 Proceedings ASCILITE 2021 in Armidale 2021
DOI: 10.14742/ascilite2021.0138
|View full text |Cite
|
Sign up to set email alerts
|

Design and development of a large Business School core interdisciplinary unit to foster blended learning during the pandemic

Abstract: The paper provides a process and design overview of a large Master of Commerce unit (from hereon referred to as 'The Unit') at a University in Australia. The skills flowing from a creative and analytical mindset have been noted as crucial in the future. The Unit develops these two mindsets as complimentary by taking a multidisciplinary approach to curriculum design. By outlining the theoretical frameworks applied in the curriculum design and development and the approaches to teaching and learning, especially d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…These programmes were created within the Faculty by means of the incorporation of technology in the curriculum, and constructive alignment. This argument supports Razeed (2021), who stated that it is believed that in explaining the theoretical frameworks used in curriculum design and development, as well as teaching and learning methodologies, other academics and instructional design teams would be afforded the ability to draw inspiration, which could be applied in their own contexts. The researcher can argue that when the initial COVID-19 pandemic lockdown restrictions were implemented at national level, as the instructional designer in the Faculty of A, she was actively engaged in the curriculum integration and interactive IMFUNDO modules redesign.…”
Section: Introductionmentioning
confidence: 55%
“…These programmes were created within the Faculty by means of the incorporation of technology in the curriculum, and constructive alignment. This argument supports Razeed (2021), who stated that it is believed that in explaining the theoretical frameworks used in curriculum design and development, as well as teaching and learning methodologies, other academics and instructional design teams would be afforded the ability to draw inspiration, which could be applied in their own contexts. The researcher can argue that when the initial COVID-19 pandemic lockdown restrictions were implemented at national level, as the instructional designer in the Faculty of A, she was actively engaged in the curriculum integration and interactive IMFUNDO modules redesign.…”
Section: Introductionmentioning
confidence: 55%
“…It was imperative that during the design phase, constructive alignment be emphasized so as not to deviate when developing the LMS module. Razeed and Werkhoven [34] argued that, based on the course's overall objectives, each topic should have its own set of learning outcomes. Simelane-Mnisi [35] emphasized that constructive alignment with the authorized curriculum design should be adhered to in an online module.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of Implementation 2, it was found that the majority (90.5%) of the academics agreed that the learning activities on the LMS motivated students to interact and engage. It was imperative that academics develop online materials that encouraged students to be actively engaged with online tasks that instilled creativity by developing creative ideas and problem-solving [34]. The results revealed that in Implementation 3, the majority (93.1%) of the academics agreed that they presented online lectures/online classes/live lecturers' webinars on Collaborate/Zoom/Google Meets.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations